School‐based surveillance for influenza vaccine effectiveness during 2014‐2015 seasons in Hong Kong. Issue 4 (25th May 2017) - Leung, Ting F.; Chan, Renee W. Y.; Kwok, Angela; Ho, Wendy C. S.; Tao, Mars K. P.; Hon, Kam L.; Cheng, Frankie W. T.; Li, Albert M.; Chan, Paul K. S.
Abstract : Background: Influenza imposes substantial healthcare burden in children, which can be prevented by vaccination. Influenza vaccination coverage varies widely among childhood populations worldwide, which has significant impact on herd immunity and usefulness of influenza vaccine. However, there are limited real‐life data on influenza vaccine effectiveness (VE) in children. Objective: This prospective study aimed to investigate clinical spectrum of childhood influenza and VE in preventing influenza in Hong Kong children. Methods: A total of 623 children were recruited from 15 kindergartens and primary schools. Parents completed a questionnaire on subjects' health and influenza vaccination history. Flocked nasopharyngeal swabs (FNPSs) were collected in biweekly school visits during 2014‐2015 influenza seasons. Influenza A and B viruses were detected and typed by molecular assays. Results: A total of 2633 FNPS samples were collected, with two or more samples being obtained from 607 (97.4%) of subjects. Thirty‐six (11.2%) subjects had influenza A or B in 2014, whereas all 19 (6.3%) subjects identified in 2015 had influenza A. Ninety‐nine subjects reported influenza‐like illness (ILI), and nine illness visits were arranged. Influenza vaccination was protective against ILI but not mild laboratory‐confirmed influenza by surveillance. Moderate overall influenza VE of 42%‐52% was observed for ILI, and subgroup analyses showed much higher VE for both ILI (70.9% vs 34.6%) and mild laboratory‐confirmed influenza (44.0% vs −6.2%) in school‐age children than preschoolers who were vaccinated within 12 months. Conclusions: Mild laboratory‐confirmed influenza infection is common in children during influenza seasons. Influenza vaccination is effective against ILI but not mild infection identified by surveillance.